10-Ethyl-3-(5-methyl-1,3,4-oxadiazol-2-yl)-10H-phenothiazine - Li-Cheng Sun; Yu-Zhen Pan; You-Gui Wang; Jian-Hui Liu (Acta Crystallographica Section E, 2012)
In the title compound, C17H15N3OS, the phenothiazine ring system is slightly bent, with a dihedral angle of 13.68 (7)° between the benzene rings. The dihedral angle between the oxadiazole ring and the adjacent benzene ring is 7.72 (7)°. In the crystal, a π–π interaction with a centroid–centroid distance of 3.752 (2) Å is observed between the benzene rings of neighbouring molecules.